KEWENANGAN PRAJURU ADAT MEMBERIKAN SANKSI ADAT KEPADA TAMIU YANG MELAKUKAN PELANGGARAN TINDAK PIDANA - Ida Bagus Gede Wahyu Pratama; Ida Bagus Alit Yoga Maheswara (VIDYA WERTTA : Media Komunikasi Universitas Hindu Indonesia, 2025)
Bali is an island tourist destination which is very famous throughout the world. This from the large number of foreign and domestic tourists who vacation on the island of Bali or who are just looking for luck in the tourism business. Where in the customary village can be seen area now there are various forms of change, one of which is in the field of pawongan (community), which is not only inhabited by native krama but has also been inhabited by migrant krama who come from different ethnicities, races, religions. The existence of tamiu in the Bajera Traditional Village, Selemadeg District, Tabanan Regency causes various population problems such as population density which continues to increase. Management and control of guests selectively and continuously must always be carried out to minimize various negative impacts, especially those whose identity is not clear. prajuru adat village collects data on every tamiu in the Bajera customary village area to minimize the various negative impacts caused by the presence of the tamiu. The purpose of this study is to find out the legal basis and mechanism for imposing customary sanctions on tamiu who commit criminal offenses. The method used is an empirical research method, with an empirical juridical approach. The data sources used in this study are primary data, secondary data, and tertiary data.